ASSESSMENT OF RED AND WHITE CLAY EVAPORATIVE RATE IN SIMULATING PERSPIRATION WITH TEXTILE - Low, Wen Pei; Tay, Lee Thin; Lee, Yee Yong; Lee, Yeong Huei; Ting, Sim Nee (Taylor’s University, Malaysia, 2023)
Urban residents in most Malaysian cities are experiencing thermal discomfort from exposure of high environment temperature due to the emergence of urban heat island situation (UHI) and climate change. To increase comfortability of urban residents, a thermal comfort study needs to be done by assessing suitable material to be used as a thermal comfort sensor that can indicate heat exposure. This study aims to fabricate white clay and red clay pots with additional textile insulation in simulating sweating process under a controlled environment. Specifically, it was done to evaluate the evaporation rate of red and white clay as well as the effects of additional textile cover towards the evaporation rate. This research covered the aspects by adding textile insulation and checking for suitability of red and white clay pots as a thermal comfort sensor material. The study was conducted by carrying out experimental procedures to measure the evaporation rate and surface temperature of the red and white clay material in the condition of with and without textile cover by using cotton and polyester textile under a controlled environment, whereby the heat exposure towards the material is regulated. The findings showed that the saturated red and white clay pots could simulate perspiration process through the evaporation rate under controlled environment and the additional cotton and polyester textile provided greater evaporative cooling effect for the material. Therefore, the relationship between the evaporation rate of porous material and sweating mechanism will be the driving force for expansion on the innovation of human thermal comfort sensor in evaluating human thermal comfort in the future to maintain comfortable surroundings.